Meningkatkan Kemampuan Motorik Halus Anak melalui Playdough: - neng rosita; Nuryati (Pendidikan Guru PAUD, FKIP, Univ Muhammadiyah Tasikmalaya, 2023)
Inappropriate learning media and methods can lead to activities that are less interesting and affect children's development, especially fine motor skills. This study aimed to determine the increase in children's fine motor development through playdough activities in the Harapan Bunda Padarincang KB. The research method used is classroom action research with a qualitative approach, the type of research is classroom action research in 3 cycles. The subjects in this study were the students of the Harapan Bunda Padarincang KB group B with a total of 12 children. Data collection techniques in the form of observation and documentation. Based on the research results obtained data, In the first cycle, the children's fine motor skills in playing playdough were still low. Most children have not been able to knead and make shapes using playdough, both when imitating shapes and printing according to the teacher's directions. This is because children still tend to like to play alone and pay little attention to the teacher's explanations. In the second cycle, the children's fine motor skills in playing playdough showed enough improvement but still did not show a significant increase. This can be seen from the results of children who get MB scores are still almost the same as those who get BSH and BSB scores, which is around 30%. Broadly speaking, learning activities went well, in cycle III the children who obtained BSH scores were 50% and BSB 44.44%. This shows that there is an increase in children's fine motor development through playdough playing activities at the Harapan Bunda KB.